DETEKSI EFEK PULAU PANAS PERKOTAAN DI KOTA PEKANBARU : KAJIAN MENGGUNAKAN TREND SUHU DAN DTR - Nazarudin, Leni (Pusdiklat BMKG, 2021)
To detect of urban heat island effect in Pekanbaru and to identify climate change, daily temperature data processing of Pekanbaru Meteorological Station in urban area and Japura Rengat Meteorological Station data in the rural region from 1982-2010 (29 years) include: minimum temperature, temperature 07.00 WIB, temperature at 13.00 WIB, maximum temperature and temperature at 18.00 WIB from 1982-2010 (29 years). Performed daily DTR (Daily Temperature Range = Tmaximum - Tminimum) trends, monthly, annual and decadal averages. The effects of urban heat island or urban heat island effect (UHIE) have occurred in Pekanbaru. Some of the indications are: annual average annual DTR decrease of 3.2 ° C per 100 years that does not occur in Japura Rengat. The narrowing of DTR in Pekanbaru is caused more by a very significant annual minimum temperature increase of 5.7 ° C per 100 years which is greater than the maximum temperature rise of 2.0 ° C per 100 years. Minimum temperature rise in Pekanbaru began to occur since 2000 in line with the development of the city. Other indications are significant rise in temperature of 18.00 hours which is 7.6 ° C per 100 years and temperature of 07.00 hours of 6.6 ° C per 100 years.